Effects of functional versus non-functional explanations for challenging behaviours on treatment acceptability - Grey, Ian M. (2004)
The study evaluated the effects of type of information naive participants received about challenging behaviour on ratings of acceptability of two multi-element treatment plans. Three groups of 20 undergraduate students with no experience of intellectual disability watched an identical 5 minute acted video of an individual with an intellectual disability engage in aggressive behaviour. Voiceover on the video differed: one group was exposed to information derived from a functional assessment, one to causal information that reflected personality and emotional factors, and the third to no causal information. Participants then rated two multielement treatment plans: one based upon functional assessment, and the other upon general non-aversive interventions. Results indicate that all groups were more accepting of the functional plan. However, individuals exposed to information derived from functional assessment were less accepting of non-functional treatment plans. Results have implications for staff cultures and the explanations for challenging behaviours that these cultures endorse